Proximal enamel thickness quantification in orthodontics for interproximal reduction: A systematic review - Arias, David; Salas Orozco, Marco Felipe (Revista Estomatología, 2022)
Background: Interproximal enamel reduction is a valuable procedure in orthodontics used in several conditions, however, not knowing the average value of proximal enamel thickness might lead to excess enamel removal and consequently to adverse effects. Objective: The objective of this systematic review is to expose the average proximal enamel thicknesses found in the literature, and the differences that might be found between different ethnicities and age groups. Search Methods: 5 electronic databases were used to perform the search. Representative keywords comprised of “enamel”, “thickness”, “orthodontics” “proximal thickness” and “quantification”; different combination of these keywords with truncation, and medical subject headings (MESH) were used. Selection Criteria: In vitro and in vivo studies, where the quantification of the proximal enamel thickness of the mesial and distal sides were evaluated independently. Data Collection and Analysis: The PICO model was used to evaluate and select the in vitro and in vivo studies. ROBINS-I tool was used to assess the risk of bias of non-randomized clinical studies and a modification of Cochrane risk of bias tool was implemented for the in vitro studies. The quality of evidence and results were evaluated using The Joanna Briggs Institute (JBI) Critical Appraisal checklist tools for Quasi-Experimental Studies. Results: Literature search identified 3298 records from 5 databases. Ultimately, nine eligible studies were included in the review. Conclusions: The proximal enamel thickness increases as we move distal through the arch and is greater on the distal side compared to the mesial side of each individual tooth. Additionally, there is no difference in the proximal enamel thickness between genders but there is between ethnicities.